iPSC Technology Revolutionizes CAR-T Cell Therapy for Cancer Treatment - Jiepu Zong; Yan-Ruide Li (Bioengineering)
Chimeric Antigen Receptor (CAR)-engineered T (CAR-T) cell therapy represents a highly promising modality within the domain of cancer treatment. CAR-T cell therapy has demonstrated notable efficacy in the treatment of hematological malignancies, solid tumors, and various infectious diseases. However, current CAR-T cell therapy is autologous, which presents challenges related to high costs, time-consuming manufacturing processes, and the necessity for careful patient selection. A potential resolution to this restriction could be found by synergizing CAR-T technology with the induced pluripotent stem cell (iPSC) technology. iPSC technology has the inherent capability to furnish an inexhaustible reservoir of T cell resources. Experimental evidence has demonstrated the successful generation of various human CAR-T cells using iPSC technology, showcasing high yield, purity, robustness, and promising tumor-killing efficacy. Importantly, this technology enables the production of clinical-grade CAR-T cells, significantly reducing manufacturing costs and time, and facilitating their use as allogeneic cell therapies to treat multiple cancer patients simultaneously. In this review, we aim to elucidate essential facets of current cancer therapy, delineate its utility, enumerate its advantages and drawbacks, and offer an in-depth evaluation of a novel and pragmatic approach to cancer treatment.